Henrick Manalastas COVID-19 Photograph - Manalastas, Henrick::::::::: (2022)
Photograph taken from a hot air balloon in Napa, California, by Henrick Manalastas who was celebrating an anniversary before the Shelter-in-Place order went into effect in Santa Clara County.